The Hedonistic Lifestyle among Students: Influence by Gratitude and Self-Control - Mujidin M Mujidin; Hindriyati Muhamat; Husnul Khotimah Rustam (Journal of Educational, Health and Community Psychology, 2022)
Hedonism refers to a lifestyle that emphasizes pleasure and luxury. Current trend among students is living in luxury and extravagance. To measure the indication, this study aimed to determine the correlation between gratitude and self-control and hedonistic life style among students. The population was students of faculty of psychology of Universitas Ahmad Dahlan, while the sample collected was class of 2019 students of 131 individuals. The sampling technique used was cluster random sampling. The students were asked to fill in three main scales, namely gratitude scale, self-control scale and hedonism scale. The data was analyzed using SPSS v16. This study was designed to describe statistical data that had been accumulated into several tables. The analysis results showed that there is a significant relationship between gratitude and self-control and hedonistic lifestyle among students. When students uphold crucial values, role models or principles, they are more likely to have better self-control and be able to suppress hedonistic urge. The findings of this study provide new insights on student lifestyle which is not as hedonistic, extravagant and lavish as initially supposed. Students that are smart in managing emotion, finance, academy, community, and communication with family are the implication of this study. Students are able to be grateful and find happiness not only in materialistic possession, but also in non-materialistic matters such as friendship and mutual sharing.